The Risk of Hippocampal Metastasis and the Associated High-Risk Factors in 411 Patients With Brain Metastases - Xie, Peng; Qiao, Hui; Hu, Huiling; Xin, Wenlong; Zhang, Huanyu; Lan, Ning; Chen, Xiaohua; Ma, Yan (Frontiers in Oncology, 2022)
Background and Aims: To retrospectively analyze the incidence of hippocampal metastasis and the associated high-risk factors in patients with brain metastases and evaluate the safety of hippocampal avoidance whole-brain radiation therapy (HA-WBRT). Methods: We retrospectively analyzed the data of patients with brain metastases diagnosed by contrast-enhanced cranial Magnetic resonance imaging (MRI) at the First Hospital of Lanzhou University from 2017 to 2020. The boundaries of the hippocampus, hippocampus + 5 mm area, hippocampus + 10 mm area, and hippocampus + 20 mm area were delineated, and the distances from the brain metastases to the hippocampus were measured. Univariate and multivariate logistic regressions were adopted to analyze the high-risk factors of hippocampal metastasis. Results: A total of 3,375 brain metastases in 411 patients were included in the analysis. The metastasis rates in the hippocampus and surrounding areas of the entire group were as follows: 7.3% (30/411) in the hippocampus, 16.5% (68/411) in the hippocampus + 5 mm area, 23.8% (98/411) in the hippocampus + 10 mm area, and 36.5% (150/411) in the hippocampus + 20 mm area. Univariate logistic regression showed that the pathological type, the number of metastases, the maximum diameter of metastases, and the volume of brain metastases were all correlated with hippocampal metastasis. Multivariate logistic regression showed that the pathological type, the number of metastases, and the total volume of metastases were correlated with hippocampal metastasis. Conclusion: The pathological type, the number of metastases, and the total volume of metastases are the high-risk factors associated with hippocampal metastasis. Small cell lung cancer (SCLC) has a significantly higher rate of hippocampal metastasis than other tumor types. The greater the number and total volume of metastases, the more likely the hippocampal metastasis. For patients with SCLC or a greater number and total volume of brain metastases, the implementation of HA-WBRT may bring a higher risk of tumor recurrence.